2020
DOI: 10.1108/emjb-03-2020-0020
|View full text |Cite
|
Sign up to set email alerts
|

Impact of skill on bi-dimensional trust within small-to-medium sized enterprises upstream relationships

Abstract: PurposeThis paper examined the deterministic and moderating impacts of skill on the behavioural (benevolence) and cognitive (credibility) dimensions of trust within small-to-medium-sized enterprises (SMEs) upstream (i.e. supplier-to-customer) relationships. A theoretically grounded research model was developed that comprised of three cognitive and three behavioural antecedents of benevolence and credibility. Impact of time (i.e. chro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 138 publications
(137 reference statements)
0
8
0
Order By: Relevance
“…Research suggests that the consequences of team members' trustworthiness and individuals' trust in teams is moderated by the temporal perspective of the relationship between parties (Jones and Shah, 2016 ). For example, Sharif et al ( 2021 ) found that trust develops and changes with time (mostly in the form of long-term relationship orientation), through the (positive or negative) impact of cognitive and behavioral actions. In the same line, Jones and Shah ( 2016 ) analyzed the relative importance of the trustor, the trustee and the trustor–trustee dyad relationship for trust building, and how the influence of each focus changes over time.…”
Section: Discussionmentioning
confidence: 99%
“…Research suggests that the consequences of team members' trustworthiness and individuals' trust in teams is moderated by the temporal perspective of the relationship between parties (Jones and Shah, 2016 ). For example, Sharif et al ( 2021 ) found that trust develops and changes with time (mostly in the form of long-term relationship orientation), through the (positive or negative) impact of cognitive and behavioral actions. In the same line, Jones and Shah ( 2016 ) analyzed the relative importance of the trustor, the trustee and the trustor–trustee dyad relationship for trust building, and how the influence of each focus changes over time.…”
Section: Discussionmentioning
confidence: 99%
“…In this changed environment, scholars have been focusing on entrepreneurial ecosystems to understand if becoming an entrepreneur is a viable career path (Llewellyn and Wilson, 2003). Other scholars also opined that entrepreneurial intention necessitates one to consider other factors, like environmental factors and the potential for economic growth in the country of concern (Lee and Peterson, 2000;Cohen and Winn, 2007;Del Giudice et al, 2017;Sharif et al, 2021). Entrepreneurial ecosystems can address all the multifarious issues affecting stability and economic growth, as well as assess the well-being of enterprises.…”
Section: Effects Of Human Capital 283mentioning
confidence: 99%
“…Other scholars also opined that entrepreneurial intention necessitates one to consider other factors, like environmental factors and the potential for economic growth in the country of concern (Lee and Peterson, 2000; Cohen and Winn, 2007; Del Giudice et al. , 2017; Sharif et al. , 2021).…”
Section: Introductionmentioning
confidence: 99%
“…It is a well-established norm that a firm can survive if it can successfully increase the number of customers, as a business' success principally depends on customer-centric activities (Rosado-Pinto and Loureiro, 2020;Sharif et al, 2021). Even in crisis, family businesses can survive if they successfully develop their customer relationship management (CRM) system (Graca et al, 2015;Ghosh et al, 2021;Tamilmani et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…It is a well-established norm that a firm can survive if it can successfully increase the number of customers, as a business’ success principally depends on customer-centric activities (Rosado-Pinto and Loureiro, 2020; Sharif et al. , 2021).…”
Section: Introductionmentioning
confidence: 99%